Physicians’ Knowledge of the Glasgow Coma Scale in a Nigerian University Hospital: Is the Simple GCS Still Too Complex? - Adeleye, Amos O.; Owolabi, Mayowa O.; Rabiu, Taopheeq B.; Orimadegun, Adebola E. (Frontiers in Neurology, 2012)
Objective The Glasgow Coma Scale, GCS, is the universal clinical means of quantifying the level of impaired consciousness. Although physicians usually receive undergraduate and postgraduate training in the use of this scale in our university hospital we are aware of some studies suggesting that the working knowledge of the GCS among practising physicians might not be as up to date as presumed. Methods We carried out an impromptu questionnaire-based survey across all specialties and levels of training of physicians in active patient care in a Nigerian foremost university hospital. Results Of the 100 physicians sampled, 98 correctly spelt out what the three-letter abbreviation, GCS, stands for. Ninety-three percent also conceded it to be an important clinical rating scale. However, only 55% to 89% of the participants correctly identified the 3 respective clinical variables, (eye opening, verbal response, and motor response), of the GCS. More particularly, the participants’ ability to itemize and correctly score all the respective components of each of the 3 clinical variables of the GCS was very poor indeed, ranging from 0% to 35% across specialties and levels of training. Performance was best for the 4-item eye opening variable and, was worst for the 6-item motor response variable. Conclusions In our university hospital, practising physicians’ working knowledge of the GCS is not as good as presumed and is dependent on the degree of the complexity of each of the three clinical variables of the scale.